2016
DOI: 10.1021/jacs.6b08273
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Surface Chemistry of Metal Organic Framework Nodes: Proton Topology of the Metal-Oxide-Like Zr6 Nodes of UiO-66 and NU-1000

Abstract: Some metal organic frameworks (MOFs) incorporate nodes that are nanoscale metal oxides, and the hydroxy-containing functional groups on them provide opportunities for introducing catalytic sites with precisely defined structures. Investigations have been done to understand the structures of these groups on nodes and node vacancies, because, in prospect, atomic-scale modulation of the composition, areal density, and/or siting of the groups would open up possibilities for exquisite tuning of the siting and perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
189
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(220 citation statements)
references
References 41 publications
30
189
1
Order By: Relevance
“…This means that two coordination vacancies on each Zr 6 node would be left and form defect sites if one formate ligand is removed (Figure S1), which could be active sites for catalytic reactions . However, current methods need to take complicated procedures and long time (several days) to reach the goal . Thus, a simple and efficient method to remove the formate ligands in the structure of MOF‐808(Zr) is highly desired.…”
Section: Introductionmentioning
confidence: 99%
“…This means that two coordination vacancies on each Zr 6 node would be left and form defect sites if one formate ligand is removed (Figure S1), which could be active sites for catalytic reactions . However, current methods need to take complicated procedures and long time (several days) to reach the goal . Thus, a simple and efficient method to remove the formate ligands in the structure of MOF‐808(Zr) is highly desired.…”
Section: Introductionmentioning
confidence: 99%
“…When atmospheric water is present, the Zr‐brick becomes hydrated: water molecules physisorb on the coordinatively unsaturated metal centers. One of the water molecules then dissociates into a hydroxyl group adsorbed on the Zr‐atom and a proton is adsorbed on the adjacent μ 3 ‐oxygen, to give a more stable structure, as discussed in literature . The unit cell of this hydrated UiO‐66 material with two missing terephthalate linkers is displayed in Figure .…”
Section: Methodsmentioning
confidence: 83%
“…These species introduce additional Brønsted sites which can play a role in reactions catalyzed by the material. A combined experimental‐theoretical work demonstrated that the topology of the OH/OH 2 defect coordinating species on the Zr 6 node‐face can be tuned with intermediate steps in which methanol replaces water on the Zr sites. Insight in the nature of active sites and the methanol substitution process was obtained, indicating that the thermodynamically most favorable structure was obtained with a node‐face containing a methoxide and an open Zr metal site .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with the TGA of STA‐26(Zr). The picture is similar to that observed for NU‐1200 and is attributed to the loss of water and hydroxyl groups from the Zr 6 O 8 clusters …”
Section: Resultsmentioning
confidence: 97%